The human plasma anellome exhibits age- and sex-dependent patterns with links to cardiometabolic health in older adults - Kane, Yakhouba; Ma, Yingying; Yan, Beibei; Zhao, Xiuli; Ge, Ting; Li, Yanpeng; Cao, Le; Zhang, Min; Wan, Zhenzhou; Zhang, Ting; Zhang, Chiyu (Frontiers in Microbiology, 2026)
The human plasma virome is dominated by anelloviruses which are increasingly associated with several clinical conditions including among others HIV-1, COVID-19, autoimmune diseases, and cardiovascular and metabolic diseases. Due to their high genetic divergence, most studies investigated human anellome at broad family or genus level. These approaches obscure the contributions of specific anellovirus species to clinical conditions. We conducted plasma metagenomics in 218 individuals from young (0–16 years) and old (63–100 years) cohorts to resolve the anellome at the species level and examine its patterns across age, sex, and associations with cytokines and cardiometabolic outcomes. Older adults exhibited near-universal anellovirus detection and significantly higher abundance compared with youth. Species-specific analysis revealed that Alphatorquevirus_homin1 and Alphatorquevirus_homin13 were markedly enriched in diseased older adults. Predictive modeling based on machine learning algorithms distinguished disease status in the young cohort with high accuracy (AUC = 0.86), but performance was limited in the elderly (AUC = 0.58), suggesting a lack of diagnostic value in advanced age. Specific species abundances and diversity were associated with stroke and coronary heart disease, while cytokine correlations revealed module-specific immune signatures: Gammatorquevirus-dominated modules associated positively with pro-inflammatory cytokines and growth factors (e.g., IL-1β, IL-15, VEGF), whereas Beta- and some Alphatorquevirus-dominated modules showed predominantly negative correlations with several inflammatory and regulatory mediators (e.g., IL-6, TNF-α, IL-10). These findings demonstrate that the anellome is influenced by age and immune status and shows associations with cardiometabolic health, although these relationships do not guarentee diagnostic or causal significance. Additonally, we found no significant differences of Human endogenous retrovirus K Env expression between disease and healthy controls. This work underscores the importance of resolving human anollome to species level in future longitudinal studies to strengthen their clinical significance and biomarker potential.